2022
DOI: 10.3389/fgene.2022.885391
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Risk Model Based on Autophagy-Related LncRNAs Predicts Prognosis and Indicates Immune Infiltration Landscape of Patients With Cutaneous Melanoma

Abstract: Cutaneous melanoma (CM) is a malignant tumor with a high incidence rate and poor prognosis. Autophagy plays an essential role in the development of CM; however, the role of autophagy-related long noncoding RNAs (lncRNAs) in this process remains unknown. Human autophagy-related genes were extracted from the Human Autophagy Gene Database and screened for autophagy-related lncRNAs using Pearson correlation. Multivariate Cox regression analysis was implemented to identify ten autophagy-related lncRNAs associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Then, based on the expression of prognostic DEGs, “ConsensusClusterPlus” script was employed to distinct the HCC samples into different gene-cluster subgroups. According to the multivariate Cox analysis and “caret” script, the independent prognostic variates were obtained and divided the HCC samples into training cohort and test cohort under the division cutoff set at 1:1 [ 31 ]. In accordance with the expression profile and coefficient of the independent prognostic variates, the risk score of each HCC sample was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Then, based on the expression of prognostic DEGs, “ConsensusClusterPlus” script was employed to distinct the HCC samples into different gene-cluster subgroups. According to the multivariate Cox analysis and “caret” script, the independent prognostic variates were obtained and divided the HCC samples into training cohort and test cohort under the division cutoff set at 1:1 [ 31 ]. In accordance with the expression profile and coefficient of the independent prognostic variates, the risk score of each HCC sample was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidence has indicated that cancer development and progression occur in concert with alterations in the TME, including stromal components and immune cells [29]. Several recent research has indicated a close relationship between cuproptosis and tumor immune in ltration in various cancers [9,17,30]. In this study, to explore how cuproptosis characterizes the TME in CC, patients with CC were divided into two subgroups based on the median CRRS, high-and low-CRRS groups.…”
Section: Discussionmentioning
confidence: 98%
“…The risk models have been used to assess the dismal prognosis of cancer patients (24)(25)(26)(27)(28). The expression levels of AC012085.2, UBXN10-AS1 and LINC00261 were significantly downregulated, while the AP004608.1, AC104667.…”
Section: Discussionmentioning
confidence: 99%